2021
DOI: 10.3390/rs13040710
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Canopy Density Parameters Time-Series for Winter Wheat Using UAS Mounted LiDAR

Abstract: Monitoring of canopy density with related metrics such as leaf area index (LAI) makes a significant contribution to understanding and predicting processes in the soil–plant–atmosphere system and to indicating crop health and potential yield for farm management. Remote sensing methods using optical sensors that rely on spectral reflectance to calculate LAI have become more mainstream due to easy entry and availability. Methods with vegetation indices (VI) based on multispectral reflectance data essentially meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 56 publications
1
19
0
3
Order By: Relevance
“…It occurs because UAV-derived CH data, unlike point-wise manually measured ones, represent a mean plant height value of an entire plot accounting for the plant density resulting from zonal statistics. Another solution to provide CH data for reliably estimating crop traits might be utilizing UAV-LiDAR data [71][72][73] and should be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs because UAV-derived CH data, unlike point-wise manually measured ones, represent a mean plant height value of an entire plot accounting for the plant density resulting from zonal statistics. Another solution to provide CH data for reliably estimating crop traits might be utilizing UAV-LiDAR data [71][72][73] and should be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al [74], using a slope-and angle-based filtering method [75] to classify UAV-LiDAR point clouds into ground and grassland, found that LiDAR underestimated the canopy height, whereas at the locations where the grassland was less than 5 cm, LiDARderived heights were overestimated. To separate ground points from points representing winter wheat as acquired by UAV-LiDAR [33], the authors argued that the cloth simulation filtering algorithm [76] had to be parameterized according to the temporal variations in the vegetation density. Since criteria for choosing the most appropriate filtering method and the optimized parameters of every filtering algorithm are lacking, we used the calculation of the total errors of morphological and interpolated-based filtering algorithms by setting different values of their parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, the 3D characterization of individual plant species of a shrubland area was achievable at the submeter scale using a UAV-LiDAR system [32]. However, the technology of UAV-LiDAR is not currently used in precision farming, despite its ability to effectively monitor canopy density [33] and fine-scale variations in crops attributes compared to UAV-optical imagery [34][35][36], which is widely employed in such applications [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Unmanned aerial vehicles (UAVs) equipped with high-resolution imaging sensors, LiDAR, multi-spectral, and hyperspectral cameras [15][16][17][18][19][20][21] have been widely used for supporting precision agriculture and digital farming applications, such as plant phenotyping [22,23], leaf area density (LAD) [24,25], leaf chlorophyll content (LCC) [26], and breeding [27] due to their versatility, flexibility, and low operational costs. A conceptual illustration of a UAV-based image acquisition system for estimation of crop parameters along with other in situ sensors and manual measurements is shown in Figure 1.…”
Section: Literature Review and Background Studymentioning
confidence: 99%